Titania supported silicotungstic acid: an efficient solid acid catalyst for veratrole acylation - Waghmare, Nilesh G.; Kasinathan, Palraj; Amrute, Amol P.; Lucas, Nishita; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
Titania supported silicotungstic acid (STA) with different STA loading (10-25 wt%) and calcination temperature (650-750 degrees C) were prepared by wet impregnation method. The catalysts have been represented by a general formula xSTiO(2)y (where x denotes wt%, S denotes STA and y denotes calcination temperature in degrees C). These catalysts were characterized by techniques such as X-ray diffraction, surface analysis, FTIR-pyridine and TPD-NH(3) and were used as heterogeneous solid acid catalysts in the liquid phase acylation of veratrole with acetic anhydride (Ac(2)O). It was found that 20STiO(2)700 gave the highest activity in acylation reaction due to its highest acidity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: acetic anhydride; Acylation; Silicotungstic acid; titania; veratrole

Comparative study on liquid phase alkylation of 2-methylnaphthalene with long chain olefins using different solid acid catalysts - Lucas, Nishita; Bordoloi, Ankur; Amrute, Amol P.; Kasinathan, Palraj; Vinu, Ajayan; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
A comparative study has been made over a variety of solid acid catalysts, which include isopoly and heteropoly ions supported on various supports such as zirconia, titania, a large variety of zeolites and a couple of mesoporous materials for liquid phasealkylation of 2-methylnaphthalene with 1-octene.All the catalyst systems were characterized by nitrogen sorption analysis, X-ray diffraction and NH(3)-TPD. Inspite of their high acid amounts zeolites gave poor catalytic performance due to their diffusional constraints; on the other hand mesoporous materials lacked diffusional constraints but due to their low acid amounts resulted in poor conversions. lsopoly and heteropoly ions supported on zirconia and titania were found to be catalytically active for the reaction due to total surface acidity. Among them, isopolytungstate supported on zirconia exhibited the best catalytic activity and was used for further optimization of reaction conditions. Excellent conversions of all olefins (>92%) with high selectivity of monoalkylmethylnaphthalene (>95%) was obtained under optimized reaction conditions. The catalyst could be recycled for several times without any obvious loss of its activity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 2-Methylnaphthalene; Alkylation; Long chain olefins; Zirconia